Relevansi Peran Filsafat dan Teknologi terhadap Pembentukan Karakter Generasi Muda di Era Globalisasi - Yuanita Nurul Nisa; Apriliyana Apriliyana; Nasikhin Nasikhin; Fihris Fihris (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: In the era of globalization, digital technology has become deeply embedded in the lives of young people, influencing not only their behaviors but also their values and self-perception. Amid this shift, philosophy offers a critical lens through which to understand and evaluate technological progress's ethical and existential implications. Objective: This study aims to explore the relationship between philosophy and technology and how their interaction affects the character formation of young people in a digitally interconnected world. Method: The research employs a qualitative approach through an extensive literature review, analyzing scholarly sources related to philosophy, technology, and youth development to identify key themes and theoretical linkages. Result: The findings reveal that the interplay between philosophical reflection and technological influence forms a complex and dynamic framework that shapes the moral, intellectual, and social dimensions of youth character in the globalized era. Conclusion: The convergence of philosophical perspectives with technological advancements can serve as a guiding force in fostering critical thinking, ethical awareness, and identity development among younger generations. Contribution: This research contributes to the discourse on youth development by emphasizing the need to integrate philosophical inquiry within educational and social frameworks to balance the rapid technological changes impacting youth. It offers strategic insights for educators, policymakers, and scholars aiming to nurture a generation that is not only technologically proficient but also ethically grounded.